Ischaemic stroke and bleeding rates in ‘real-world’ atrial fibrillation patients - Ogilvie, Isla M.; Welner, Sharon A.; Cowell, Warren; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2011)
Stroke prevention guidelines recommend oral anticoagulants (OAC) for atrial fibrillation (AF) patients at moderate/high risk of stroke, and antiplatelet or no therapy for those at low/moderate risk. Outcomes for AF patients receiving antiplatelet/no therapy in ‘real-life’ clinical practice were explored. This study compared clinical event rates (stroke/bleeding) for AF patients treated with OAC therapy, antiplatelets or no therapy in usual clinical practice to event rates in OAC-treated AF patients from optimally-monitored ‘real-life’ settings (anticoagulation clinics). We searched biomedical literature (1994–2010) using PubMed to identify ‘real-world’ studies of clinical event rates for AF patients receiving OAC therapy, antiplatelets, or no therapy; event rates were extracted for each treatment and setting. We identified 136 studies of thromboembolic events and 86 of bleeding events. Ischaemic stroke rates (30 studies) were higher for AF patients receiving no therapy (median: 4.45/100 person-years; range: 0.25–5.9) or antiplatelet-therapy (median: 4.45/100 person-years; range: 2.0–10) compared to OACtreated patients monitored in anticoagulation clinics (median: 1.72/100 person-years; range: 0.97–2.00), or from a non-specialized setting (median 1.66/100 person-years; range: 0–4.9). Major bleeding rates (32 studies) for patients receiving antiplatelet/no therapy were similar to OAC-treated patients from both clinical settings. As in randomised clinical trials, AF patients in ‘real-world’ clinical practice receiving antiplatelet/no therapy have higher rates of ischaemic stroke than OAC-treated patients. Antiplatelet/no therapy was associated with similar bleeding rates to OAC therapy. Increasing utilisation of anticoagulants in clinical practice could improve patient outcomes.
Keywords: Atrial fibrillation; oral anticoagulation; antiplatelets; stroke; bleeding